2022
DOI: 10.46520/bddkdergisi.1178359
|View full text |Cite
|
Sign up to set email alerts
|

Türk Sigorta Sektörünün 2002-2021 Dönemi için MEREC, LOPCOW, COCOSO, EDAS ÇKKV Yöntemleri ile Performansının Değerlendrilmesi

Abstract: Bu çalışmanın amacı Türk sigorta sektörünün 2002-2021 dönemi performansının değerlendirilmesidir. Çalışmada Türk sigorta sektörünün performansının değerlendirilmesi için altı adet performans kriteri belirlenmiştir. Çalışmada iki farklı kriter ağırlıklandırma yöntemi ve iki farklı performans değerlendirme yöntemi olmak üzere toplam dört farklı yöntem kullanılmıştır. Kriterlerin ağırlıklandırılmasında MEREC ve LOPCOW yöntemlerinden faydalanılmıştır. Performans değerlendirmesinde COCOSO ve EDAS yöntem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…MEREC yöntemi kriter ağırlıklarını belirtirken, kriterlerin kaldırma etkilerine, başka bir ifadeyle herhangi bir kriter için önem ağırlık hesaplaması yapılırken, bu kriter devre dışı bırakılarak toplam kriter ağırlığında meydana gelen değişime bakılır. (Bektaş, 2022). MEREC yönteminin altı aşamadan oluşan çözüm prosedürü aşağıdaki şekilde özetlenmiştir (Toslak vd., 2022):…”
Section: Merecunclassified
“…MEREC yöntemi kriter ağırlıklarını belirtirken, kriterlerin kaldırma etkilerine, başka bir ifadeyle herhangi bir kriter için önem ağırlık hesaplaması yapılırken, bu kriter devre dışı bırakılarak toplam kriter ağırlığında meydana gelen değişime bakılır. (Bektaş, 2022). MEREC yönteminin altı aşamadan oluşan çözüm prosedürü aşağıdaki şekilde özetlenmiştir (Toslak vd., 2022):…”
Section: Merecunclassified
“…The MEREC method was introduced by Keshavarz-Ghorabaee et al ( 2021) for the objective determination of criterion weights. The steps for implementing the MEREC method are listed below (Bektaş, 2022;Ghosh & Bhattacharya, 2022).…”
Section: Merecmentioning
confidence: 99%
“…Furthermore, studies can be found in the literature that have used both the MEREC and CoCoSo methods together. MEREC and CoCoSo methods were used together in decision problems such as performance evaluation of insurance companies (Bektaş, 2022), selection of waste and recycled materials for road construction (Marinkovic et al, 2022), aircraft selection for flight schools (Özdağoğlu et al, 2022), assessment of urban transportation plans (Simic et al, 2022), financial performance evaluation of lodging and tourism industries (Ghosh & Bhattacharya, 2022), evaluation of countries' innovation performance (Ecer & Ayçin, 2023), and assessment of airport service quality (Sümerli Sarıgül et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though many studies in which corporate sustainability performance is measured by MCDM methods have found their place in the literature (Rabbani et al, 2014;Alp et al, 2015;Rao, 2021) no research has been found in which corporate sustainability performance is measured with MEREC or CoCoSo methods. Although there are studies in the MCDM literature in which these relatively new methods are used together (Bektaş, 2022;Marinkovic et al, 2022;Simic et al, 2022), it can be considered as a new combination for corporate sustainability performance. In these respects, the study produces original results and contributes to the literature.…”
Section: Introductionmentioning
confidence: 99%